PENYERAHAN PEKERJAAN KEPADA PIHAK KETIGA (OUTSOURCHING) DALAM BIDANG JASA BATU BARA DAN AKIBAT HUKUMNYA (STUDI DI PT. EPISI SUCOFINDO) - Sunariyo sinariyo (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
Abstract           Labor conditions were relatively stable in the three decades of the New Order regime, the system of labor laws Indonesia shocked by the transformation suddenly of a model law Labour "corporatist" with the support of a strong state behind him, into a system that is based on the market and let the workers face " face to face "with the power of capital. These conditions completely new situation for the lives of workers in Indonesia. A drastic change like that really happen after the fall of the New Order regime.Industry downturn in Indonesia especially in Samarinda coal field resulted in termination of employment (FLE) heavily in the early to mid 2000s. In fact, Indonesia is the only Southeast Asian country that is experiencing Foreign Direct Investment (FDI) when it is negative, it means that out of the Indonesian capital is greater than the amount of incoming capital. According to data reported by the World Investment Report 2004, in 2003 the flow of capital out of Indonesia amounted to US $ 597 million, while inflow amounted to only about US $ 130 million. This puts Indonesia at position 139 out of 144 countries ranked sixth investment objective or investment destination bottom.